Valoração de serviços ecossistêmicos:: por que e como avançar? (Sustainability in Debate, 2013)
The main goal of this paper is to contribute to the methodological improvement of the ecosystemservices valuation process. The basic hypothesis adopted was that it should consider using theecological-economic modeling as a basic tool required to better understand the ecologicaldynamics involved and incorporate other values of ecosystem services that otherwise would notbe captured. As an important management tool, it is vital to go beyond with proposals forimproving the ecosystem services valuation, in order to overcome its reductionist bias. In thissense the most important contribution of this paper is the proposal of a ecological-economicvaluation approach, which is aimed at integrating the stricto sensu valuation to the more generalanalysis of changes in ecosystem services flows (ecosystem assessment) and its effects on economicvariables.